2020
DOI: 10.3390/foods9030251
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Umami Taste in Sous-Vide Beef by Chemical Analyses, Equivalent Umami Concentration, and Electronic Tongue System

Abstract: Behaviour of umami compounds that are associated with non-volatile compounds on slow cooking regimes remains less explored. This study aims to assess the ability of the electronic tongue system on the umami taste from sous-vide beef semitendinosus. The identification was based on the taste-enhancing synergism between umami compounds 5’-nucleotides (IMP, GMP, AMP, inosine, and hypoxanthine) and free amino acids (glutamic and aspartic acid) using the estimation of equivalent umami concentration (EUC) and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Our results showed that meat cooked at 65 • C for 8 h and 12 h produced slightly intense to moderately intense beef flavour regardless of the treatments. Flavour of meat is impacted by the type and concentration of the volatile compounds produced during cooking [64]. The flavour in sous vide cooked beef mainly depends on cooking temperature [39].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that meat cooked at 65 • C for 8 h and 12 h produced slightly intense to moderately intense beef flavour regardless of the treatments. Flavour of meat is impacted by the type and concentration of the volatile compounds produced during cooking [64]. The flavour in sous vide cooked beef mainly depends on cooking temperature [39].…”
Section: Discussionmentioning
confidence: 99%
“…The highest EUC found in Rhodomonas salina was reported to be 23.4 g MSG/100 g AFDW when cultivated at pH 8.5 and 30% salinity [31]. In Sousvide beef, the EUC can rise as high as 53.3 g MSG/100 g AFDW [32]. In some savoury mushrooms, which are known for their umami flavour, the EUC ranges between 0.12 and 4465 g MSG/100 g AFDW in the fruit body and 1.92 and 460 g MSG/100 g AFDW in the mycelia [33].…”
Section: Protein and Amino Acid Dynamicsmentioning
confidence: 99%
“…Del Pulgar et al [22] reported similar results, where sous vide cooking resulted in lower water loss than conventional cooking. is is most likely due to the vacuum packaging used for sous vide cooking at 60°C, which prevents the loss of free water [37]. e pH of pork was inversely related to its cooking loss.…”
Section: Proximate Analysis Ph Expressible Drip and Cookingmentioning
confidence: 99%